The Role of Between Scenario Quality and Prior Knowledge on the Effectiveness of Tutorial Discussions in Problem-Based Learning (PBL): Literature Review - Mu'izabby, Iffah Salma; Oktafany, Oktafany; Ratna, Maya Ganda; Lisiswanti, Rika (Medula, 2024)
Problem-Based Learning (PBL) is a learning method that puts students at the centre of the learning process, encouraging them to learn independently through problem solving. One of the main approaches in PBL is tutorial discussion, which plays an important role in promoting deep learning. The effectiveness of tutorial discussions is influenced by three main aspects: the quality of the problem scenario, students' prior knowledge, and tutor performance. The scenario should be authentic, relevant to the students' level of understanding, and able to stimulate independent learning. Students' prior knowledge also affects their contribution to the discussion, as adequate understanding allows for more active engagement. In addition, the tutor's role in facilitating the discussion also influences the success of the PBL method. The quality of the scenario and prior knowledge play an important role in the effectiveness of Problem-Based Learning (PBL) discussions, although their relationship is not always statistically significant. The quality of a well-designed scenario can stimulate meaningful discussions, motivate students, and support the achievement of learning objectives. Prior knowledge, while not necessarily determining the success of the discussion, influences how students integrate new information. Groups with lower prior knowledge can show higher discussion effectiveness through active exploration. Overall, the effectiveness of PBL is influenced by the interaction between the quality of learning design and student characteristics, suggesting the need for a holistic approach in designing PBL scenarios.